Molecular Mechanism of Resistance in Kenyan Groundnut (Arachis Hypogea) Against Aspergillus Flavus Infection. - Okayo, Robert Odhiambo (Jooust, 2023)
Pathogenesis of Aspergillus flavus on groundnut is a key concern on human health. Much success has been achieved by the application of atoxigenic strains of A. flavus, improvement of cultural practices and chemical application for controlling aflatoxin contamination in groundnuts. Development of aflatoxin resistant cultivars is more sustainable strategy for ensuring quality food. However, there is lack of sources of resistance and biological information for molecular and biotechnology applications. This study was therefore conducted to identify the sources of resistance and contribute to the understanding of genes involved in A. flavus resistance in groundnuts. Pure isolates of A. flavus was isolated using morphological and molecular approaches. Thirty gene bank accessions were evaluated in the green house and the pods harvested for bioassay in the laboratory. Differentially expressed genes in response to A. flavus infection were identified through microarray. Eight genes were selected for addition scrutiny using real time PCR at a seedling stage at an interval of 2 days within a 7-day period. Five isolates were identified to be pure toxigenic strain of A. flavus. Screening the genotypes reveal a highly significant (P<0.001) difference of aflatoxin contamination, incidence and severity. The incidence had a mean of 23.5% and a range between 7.5% to 48.5%. All except genotype 12 (GBK005111) had percentage incidence greater than 10%. The severity index had a mean of 0.25 and a range of 0.049 to 0.58. Genotype 12 (GBK005111) had the lowest mean rating for severity while genotype 1 (GBK000423) had the highest. Hierarchical clustering based on the incidence, severity and aflatoxin contamination grouped the genotypes into 3 with cluster 3 containing 7 promising genotypes that had lower levels of infection and contamination. A large-scale microarray analysis identify total of 163 genes that were differentially expressed as determined by log2 ratio > 1.5 of the fold change out of which 63 genes were upregulated while 100 genes were down regulated. 57 genes differentially expressed had a putative function assigned to them while 106 genes were hypothetical. The upregulated genes with putative functions were grouped into 9 functional categories based on dominant biological function. The eight selected genes reveal an intricate network of gene expression patterns in a sequential order in both resistance and susceptible lines at a seedling stage with the peak level indicating the crucial time for gene action. This study successfully cultured and isolated 5 toxigenic isolates of A. flavus and submitted them to the gene bank where they were allocated accession numbers LC567154, LC567155, LC567156, LC567157 and LC567158. Different response to A. flavus and aflatoxin contamination exist in Kenyan groundnuts germplasm held in gene bank. GBK005111 (genotype 12) exhibited low values for incidence, severity and lower aflatoxin contamination accepted by the Kenya Standards. This genotype represents a relevant tool for the breeding program for resistance to A. flavus as a potential gene donor. The transcriptomics analysis reveals differential gene expressions and the transcripts upregulated are confirmed to be involved in resistance mechanisms. These genes are key tools in identifying biomarkers for breeding, potential candidate genes for transgenic manipulation, and will help in understanding complex plant-fungal interaction for future downstream research.
Keywords: Genes; Molecular Mechanism of Resistance in Kenyan Groundnut (Arachis Hypogea)